Refugees and the violence of welfare bureaucracies in Northern Europe - Abdelhady, Dalia; Gren, Nina; Joormann, Martin (Manchester University Press, 2020)
Given the significant similarities and differences between the welfare states of Northern Europe and their reactions to the perceived 'refugee crisis' of 2015, the book focuses primarily on the three main cases of Denmark, Sweden and Germany. Placed in a wider Northern European context - and illustrated by those chapters that also discuss refugee experiences in Norway and the UK - the Danish, Swedish and German cases are the largest case studies of this edited volume. Thus, the book contributes to debates on the governance of non-citizens and the meaning of displacement, mobility and seeking asylum by providing interdisciplinary analyses of a largely overlooked region of the world, with two specific aims. First, we scrutinize the construction of the 2015 crisis as a response to the large influx of refugees, paying particular attention to the disciplinary discourses and bureaucratic structures that are associated with it. Second, we investigate refugees' encounters with these bureaucratic structures and consider how these encounters shape hopes for building a new life after displacement. This allows us to show that the mobility of specific segments of the world's population continues to be seen as a threat and a risk that has to be governed and controlled. Focusing on the Northern European context, our volume interrogates emerging policies and discourses as well as the lived experiences of bureaucratization from the perspective of individuals who find themselves the very objects of bureaucracies.